PRE-SERVICE TEACHERS' PERCEPTION OF THE USE OF GEOGEBRA IN TEACHING AND LEARNING GEOMETRY IN THE COLLEGES OF EDUCATION, GHANA - Zutaah, Puotier; Ondigi, Samson Rosana; Miheso-O'Connor, Marguerite Khakasa (JOHME: Journal of Holistic Mathematics Education, 2023)
The introduction of technology has given opportunities and made it easy for educators to utilize it in various ways, including in the field of education, as an instrument to support the teaching and learning of mathematics. GeoGebra is one of the mathematical software programs that can be effectively used in delivering mathematics lessons. GeoGebra is computer software that supports the teaching and learning of mathematics subjects, especially algebra, calculus, geometry, probability, and statistics. The objectives of this systematic analysis were to investigate pre-service teachers' perceptions and benefits of using GeoGebra to teach geometry. This study used a quantitative research design to review published articles from 2011 to 2021 related to the research objectives. This investigation purposefully sampled 17 published articles out of the over 200 articles found. The study used Google scholar, Google, and Sci Direct as the search engines to gather data using the keywords. The selected articles were validated using content analysis. This investigation selected the 17 articles for data analysis based on the research design, location, area of research, research focus and the type of technology applied. The findings of this study disclosed that pre-service teachers had the following perceptions regarding learning geometry with GeoGebra: GeoGebra enhances the teaching and learning of geometry, it helps learners to have positive perceptions concerning GeoGebra integration, GeoGebra improves learners' interest, motivation, and willingness to learn geometry. Also, it motivates learners to interact among themselves. Nevertheless, some benefits were identified as follows: GeoGebra increases students’ academic performance, develops learners' confidence in learning geometry, makes the learning of mathematics enjoyable, and helps learners to conceptualize abstract concepts in mathematics. Based on the findings of this study, it is concluded that GeoGebra is effective for teaching and learning geometry. This study recommends that mathematics educators should embrace GeoGebra software in the teaching and learning of geometry at the college level of education. Additionally, the Ministry of Education should enforce the integration of GeoGebra in the delivery of mathematics lessons.